The Assessment of Nurses’ Knowledge and Practices about Fluid and Electrolytes Monitoring and Administration among Cardiac Surgery Patients: A Case of Punjab Institute of Cardiology - Aslam, Shumaila; Afzal, Muhammad; Kousar, Robina; Waqas, Ali; Gilani, Syed Amir (International Journal of Applied Sciences and Biotechnology, 2017)
Background: In order to maintain the health, the homeostasis dynamics and balance process is most important. Among the critically ill cardiac surgery patients the homeostasis is imbalance and results in insufficient tissues perfusion and many organs of the body lead to the failure condition. It is necessary to monitor actively the intake and output during electrolytes administration in the cardiac surgery patients. Objectives: To assess the knowledge and practice of the registered nurses about fluid and electrolytes monitoring and administration in the cardiac surgery patients. Methodology: This study is of descriptive and cross sectional study design. The questioner of knowledge and practices regarding fluid and electrolytes administration was adopted from the article of Vijayan (Vijayan, 2011) which is based on 5-point Likert scale. The data was collected from 208 nurses of Punjab Institute of Cardiology, Lahore, Pakistan. Conclusion: The findings of the current study show that the nurses have poor knowledge and practices of nurses, so, public hospital’s administration should focus on the strategies and activities which become helpful to increase the knowledge and practices of nurses regarding fluid and electrolytes administration. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 208-215